Digital transformation in tourism: Modes for continuing professional development in a virtual community of practice - Susanne Marx; Sandra Flynn; Mika Kylänen (Project Leadership and Society, 2021)
Continuing professional development (CPD) is a key challenge in enabling digital transformation in the tourism sector, and its networked service provided by small and medium-sized enterprises. Communities of Practice mirror this network approach towards learning, facilitated digitally as a Virtual Community of Practice (VCoP). This research examines how an inter-organisational VCoP on digital transformation in tourism could be delivered. Following a survey strategy (n = 244), the study demonstrates that both individual interests and organisational challenges define the shared domain of interest and constitute the motivational factors for joining a VCoP. We identify four roles of engagement: knowledge provider, practitioner, facilitator, and learner, appreciating both self-paced learning and peer interaction facilitated by multiple digital tools. The organisational type as an exemplary characteristic of members correlates with various VCoP elements. An open member structure results in volatile requirements of the VCoP, why we finally discuss agile project management methodology for VCoP delivery.